Analisis Pengetahuan dan Kecemasan Penderita HIV/AIDS terhadap Covid 19 - Marnila Yesni; Dwi Kartika Pebrianti (Prosiding Seminar Kesehatan Nasional, 2022)
Transmission of this virus can be through direct contact, for example by droplets, or indirectly, for example by touching objects that are contaminated with the virus. The clinical management of COVID-19, the patient's comorbid history is important because patients with co-morbidities can worsen the condition of COVID-19 and have a poor disease prognosis. Several comorbid conditions include Diabetes Mellitus, geriatric-related diseases, kidney disease, autoimmune disease and other chronic diseases. Literature studies that have been conducted found that people with HIV (ODH) are susceptible to contracting COVID-1 disease. Lack of knowledge accompanied by anxiety will affect the lives of HIV/AIDS sufferers during the pandemic. This study aims to describe the knowledge and anxiety of HIV/AIDS sufferers related to COVID-19. The method used in this research is descriptive analytic. The population in this study were all ODHA at the Kanti Sehati Foundation with a total sample of 62 respondents, using univariate data analysis. The results of the study obtained 41.9% had sufficient knowledge about Covid 19 and 43.5% experienced a mild level of anxiety, 3.2% experienced a moderate level of anxiety. the use of information technology in learning methods, especially online, by adjusting the development of information media